Synthesis and characterization of red pigment from acid regeneration plant (ARP) by-product via rod milling process - Woon, Hai Song; Naidu, Keerthan; Ewe, Lay Sheng; Ean, Lee Woen; Lim, Kean Pah (Chiang Mai University, 2024)
Iron o xide waste from acid regeneration plants (ARP) is often discarded due to its non-profitability. This research aims to introduce a value-added process to convert iron oxide waste into red pigment via rod milling process. The iron oxide waste collected from ARP was grinded with a rod milling machine at 30 rpm for 24 hours. The ground product was then mixed with industrial-grade red pigment in various ratios. The mixed samples were then rod-milled again into ultra-fine particles. A total of seven samples were prepared, applied onto a canvas and analysed by energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) methods. From the analyses, the existence, composition, and orientation of iron oxide were established. The waste-derived red pigments were subsequently subjected to particle size analysis on a scanning electron microscopy (SEM) platform, with results showcasing the efficiency of the rod milling process. Colour-related properties of the samples before and after canvas application were investigated using the L*a*b* system with a chromameter. Empirical outcomes indicated that the a* value plays an important role in determining the redness of the sample. Overall, the a* values obtained were above 15 and gradually increased in accordance to the amount of industrial-grade red pigment added. The oil absorptivity of red pigments was also tested via an oil absorptivity test. Notably, the assay signified that particle size and porosity affect the amount of oil that can be absorbed by the pigment.